Analysis of Population Density, Economic Growth Rate, and the Number of Motorized Vehicles on Environmental Qual-ity in Indonesia - Intan Angelisa; M. Ridwansyah; Jaya Kusuma Edi; Zainul Bahri (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study, entitled